STABILITAS PONDASI BORE PILE UNTUK TOWER TIPE 4EE6+33 SLIM PADA RELOKASI SALURAN UDARA TEGANGAN TINGGI DK 129+920: - Putra, Sulis Adi (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
Electricity transmission towers require a solid foundation to support the structural load, one electricity transmission tower line is often located on diverse land conditions, such as rice fields, forests, plantations, and residential areas. With the closer location of towers to residential areas and limited land, slim type transmission towers that have minimal tower leg spans are an option for space efficiency. The purpose of this study is to determine the soil bearing capacity, tensile force, compressive force, soil settlement and iron diameter used in bore pile. This bore pile foundation stability analysis is located in Pasawahan Village, Dayeuhkolot, Bandung Kidul with tower type 4EE6+33 slim with a bore pile diameter of 60 cm and a depth of 17m. The analysis methods used are Reese & Wright Method, Converse-Labarre Method and janbu, Bjerum, and kjaernsli Method. The results of the analysis of the bore pile tower foundation type 4EE6 + 33 slim show a compressive force of 56.1 tons, a tensile force of 10.98 tons. While the analysis of the 60 cm diameter bore pile foundation at a depth of 17 meters shows the bearing capacity of the pile blanket of 3474.429 kN/m2, the bearing capacity of the pile tip of 721.286 kN/m2, the ultimate bearing capacity of 4159.714 kN/m2 and the allowable bearing capacity of 953.314 kN/m2 and the consolidation settlement analysis obtained results of 24.79 mm < 25 mm. Reinforcement calculation on bore pile tower foundation type 4EE6+33 slim bore pile reinforcement used 12 D19 mm and spiral reinforcement.